The influence of the Mediterranean diet on glucose metabolism - Mielniczek, Katarzyna (Journal of Education, Health and Sport, 2021)
Introduction: Insulin resistance is the first stage of diabetes development. It has been defined as a dysmetabolic state in which the biological response of target tissues (particularly liver, muscle and adipose tissue) to circulating insulin is impaired. This leads to hyperinsulinemia, which in turn leads to obesity and type 2 diabetes (T2D). The basic ingredients of the Mediterranean diet, such as fruit, vegetables, fish rich in fat, extra virgin olive oil, tree nuts, red wine, have been defined in the functional food model by the natural content of nutraceuticals such as polyphenols, terpenoids, flavonoids, alkaloids, sterols and unsaturated fatty acids. Purpose of the work : Demonstrate the beneficial effects of implementing the Mediterranean diet in patients with insulin resistance or type 2 diabetes. The appropriate samples were accessed using a search engine in the PubMed database. The reviews and meta-analyzes published over the last 10 years were used. Results: After changing the diet to a diet rich in these nutrients, a greater improvement in IR was shown in obese people compared to other diets. In addition, dietary polyphenols demonstrated clinically significant benefits in metabolic and microvascular functions leading to lowering of fasting cholesterol and glucose, and anti-inflammatory and antioxidant properties in high-risk and T2DM patients. Conclusions: Mediterranean diets with the addition of extra virgin olive oil or nuts reduced total body weight and improved glucose metabolism.